2004
DOI: 10.1104/pp.103.036822
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Locus Analysis of Growth-Related Traits in a New Arabidopsis Recombinant Inbred Population

Abstract: Arabidopsis natural variation was used to analyze the genetics of plant growth rate. Screening of 22 accessions revealed a large variation for seed weight, plant dry weight and relative growth rate but not for water content. A positive correlation was observed between seed weight and plant area 10 d after planting, suggesting that seed weight affects plant growth during early phases of development. During later stages of plant growth this correlation was not significant, indicating that other factors determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
114
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 41 publications
14
114
0
Order By: Relevance
“…In addition, we included the accession Shakdara (Sha) that is assumed to contain a weak FLC allele (Gazzani et al 2003;Michaels et al 2003). This is in agreement with the absence of a late-flowering Sha allele at the FLC locus in populations made from crosses with Sha (Loudet et al 2002;El-Lithy et al 2004). …”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…In addition, we included the accession Shakdara (Sha) that is assumed to contain a weak FLC allele (Gazzani et al 2003;Michaels et al 2003). This is in agreement with the absence of a late-flowering Sha allele at the FLC locus in populations made from crosses with Sha (Loudet et al 2002;El-Lithy et al 2004). …”
Section: Resultsmentioning
confidence: 78%
“…Kas-2 and Kond have late alleles at the FRI locus, which is at least functional in Kond (Gazzani et al 2003;Michaels et al 2003;Hagenblad et al 2004). Active FRI alleles may confer lateness without FLC, as was also found in Sha-derived populations (Loudet et al 2002;El-Lithy et al 2004). In the Ler 3 An-1 population, a novel locus was also identified at the top of chromosome 4, for which An-1 accelerates FT.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Segregation distortion at MAF2: Several studies have reported a flowering-time QTL in the vicinity of the MAF locus, as well as a segregation distortion favoring the early flowering allele (Loudet et al 2002;El-Lithy et al 2004Simon et al 2008). To determine the frequency of the insertion alleles relative to MAF2-Ler, we analyzed the BC 5 F 2 segregating populations.…”
Section: Resultsmentioning
confidence: 99%